ANALISIS BALANCED SCORECARD SEBAGAI SARANA PENGUKURAN KINERJA PERUSAHAAN (Studi Kasus pada Pabrik Gula Pesantren Baru Kediri) - Ami Dhatul Solichah (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
Measurement of the performance of a company adapted to the conditions and forms of enterprise. Measurements should be able to see all sides of a part, both in terms of customers, in financial terms, in terms of production and in terms of employees. Measurement of performance through strategic management approach is summarized in a strategic measurement Balanced Scorecard. Balanced Scorecard measure performance through four perspectives, such us financial perspective, customer perspective, internal business process and learning and growth perspective. Measurement of performance against PG Pesantren approach the decree of the Minister of State-Owned Enterprises No. Kep-100/MBU/2002 to assess the soundness of state-owned enterprises. Results stated that the company's performance during the year 2011-2013 in financial terms with healthy predicate